Is There a Bias in the Diagnosis of Borderline Personality Disorder Among Lesbian, Gay, and Bisexual Patients?. (April 2021) - Rodriguez-Seijas, Craig; Morgan, Theresa A.; Zimmerman, Mark
High prevalence of borderline personality disorder (BPD) diagnosis is observed among sexual minority samples. It is unclear if sexual minority individuals are systematically diagnosed with BPD at higher rates than heterosexual individuals, and if potential diagnostic disparity can be explained by differences in maladaptive personality domains. Utilizing data from partial hospital patients ( N = 1, 099) the current study explored (a) differences in the frequency of diagnosis of BPD based on sexual orientation, (b) whether disparities explained differences in psychopathology across groups, and (c) the congruence between traditional methods of BPD diagnosis (i.e., clinical assessment) versus diagnosis based on elevations in self-reported maladaptive personality domains consistent with the alternative model for personality disorders. Sexual minority individuals were more likely to be diagnosed with BPD than heterosexual individuals (odds ratio [ OR ] = 2.43, p < .001), even after controlling for differences in clinical correlates of BPD diagnosis (age, gender, comorbid posttraumatic stress disorder, maladaptive personality domains; OR = 1.59, p < .05). Diagnostic disparity was highest for bisexual compared with heterosexual patients. These results suggest that clinicians may be predisposed to provide a BPD diagnosis to sexual minority patients that is independent of presenting psychopathology and bear important implications for future research aimed at discerning whether such predisposition is due to measure or clinician bias.